The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1995
DOI: 10.1179/sic.1995.40.1.51
|View full text |Cite
|
Sign up to set email alerts
|

The natural and accelerated aging of an acrylic artists' medium

Abstract: Changes in appearance and in the chemical and mechanical properties of films of Liquitex acrylic gloss medium, a commercial artists' medium based on an acrylic polymer dispersion, have been studied during natural aging in the dark and in accelerated thermal and light exposure tests. In dark storage at room temperature and humidity, the films acquire a haze and slight yellow discoloration in a few weeks, while the tensile properties stabilize only after film formation has progressed for about 50 days. Crosslink… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 30 publications
0
12
0
1
Order By: Relevance
“…Mechanisms that may have affected the coating, stored in office conditions inside a plastic pocket with limited air circulation and no light exposure, are uncertain but could be related potentially to the aging of the sodium polyacrylate additive in the coating. Various natural aging effects, including changes in solubility and swelling, have been shown to take place in films of commercial acrylic polymer dispersion [24].…”
Section: Coating Propertiesmentioning
confidence: 99%
“…Mechanisms that may have affected the coating, stored in office conditions inside a plastic pocket with limited air circulation and no light exposure, are uncertain but could be related potentially to the aging of the sodium polyacrylate additive in the coating. Various natural aging effects, including changes in solubility and swelling, have been shown to take place in films of commercial acrylic polymer dispersion [24].…”
Section: Coating Propertiesmentioning
confidence: 99%
“…Based on the DSC curve of Edelwachs at t0 ( Figure 9 a), some considerations can be made [ 3 , 66 , 67 , 68 , 69 ]: The glass transition temperature (Tg) occurs at about 36 °C: This value is probably due to the influence of the wax components mixed with acrylic monomers. The endothermic process at 82 °C refers to a solid–liquid phase change (melting) of the waxy components, where no mass variations are involved.…”
Section: Resultsmentioning
confidence: 99%
“…for other 7 days). Ageing conditions were adjusted based on those previously used for the natural and accelerated ageing of acrylic-based artist's media [17][18][19].…”
Section: Mock-up Sample Preparationmentioning
confidence: 99%
“…It is noted that other studies [22,23] using techniques with even lower detection limits, such as XPS, have identified silicone emulsifier residues on paint films after clearance. 17 The PVP absorption of the PVA/PVP based TT14 thin gel is an upward band in reflectance mode [40]; therefore, yellow-red pixels were expected where residues were present. As seen in Fig.…”
Section: Cleaning System Residue Evaluation-mock-upsmentioning
confidence: 99%